Efficient Deep-Blue Light-Emitting Diodes Through Decoupling of Colloidal Perovskite Quantum Dots - Jang, Kyung Yeon (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 The Author(s). Advanced Materials published by Wiley‐VCH GmbH.